Compendium of partners for scaling gender and social inclusion - Mehar, Mamta (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
To scale gender and social inclusive climate-smart agriculture (CSA), current and potential collaborative partners will need to address gender norms. In an effort to identify these partners, the CGIAR Research Program on Climate Change, Agriculture and Food Security’s Gender and Social Inclusion and Climate Services Flagship supported the collection of information about potential scaling partners, including government agencies, research institutes, NGOs, and women’s and civil society organisations at the global, regional, national, and sub-national levels in CCAFS countries.